KEBIJAKAN INVESTASI ASING DI INDONESIA DALAM MENGHADAPI ASEAN ECONOMIC COMMUNITY 2015 - Mia Aidilla; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
ASEAN Economic Community (AEC) 2015 has become part of the international system. ASEAN Economic Community was formed to create a single market and production is characterized by a free flow of goods, services, investment, skilled labor and freer movement of capital. The problem occurs that foreign investments are rae and not much to invest in indonesia, so the discussion is needed about the indonesia government policies issued by foreign investment or the so-called FDI ( Foreign direct investment ).The purpose of this study is to describe and explain indonesia make foreign investment policy. This study also aims to see indonesia to prepare for the MEA ( Masyarakat Economic ASEAN).This study uses the theory of liberalism, the methods used, explanatory research method that seeks or intends to disclose and explain the phenomenon in detail and useful, in assesing the problems occurred. The development of foreign investment in indonesia has not grown overall despite some initial potential which is available for viewing and favored investors, particularly in agriculture and mining.The role of direct investments to areas of indonesia. Foreign investmentpolicy is to establish a technical institute that addresses foreign investment, promoting potential. Obstacles in attracting foreign investment in indonesia is still slightly completeness and investment regulations that do not exist.Key Word : ASEAN Economic Community 2015, theory of policy, implementation, foreign investment, local regulation